The Sargasso Sea Commission: An Evolving New Paradigm for High Seas Ecosystem Governance? - Freestone, David (Frontiers in Marine Science, 2021)
The Sargasso Sea is to be found within the North Atlantic Subtropical Gyre. Its borders are the major ocean currents. These boundaries shift with these currents, but there is a core area that covers approximately 2 million square nautical miles situated around the Bermuda archipelago, the majority of which is beyond the national jurisdiction of any State. Ten governments have now signed the 2014 Hamilton Declaration on Collaboration for the Conservation of the Sargasso Sea, which mandated the Government of Bermuda to appoint the members of the Sargasso Sea Commission—the first such body to take on a stewardship role for a high seas ecosystem. The Commission has committed to working with the existing international organizations with jurisdictional competences over a myriad of high seas activities. This paper will examine the work of the Commission and lessons learned over the past decade; it will discuss its possible role as a “boundary spanning” organization and look forward to its future in the light of recent grants from the Global Environment Facility (GEF) and the Fonds Francais pour l’Environnement Mondial (FFEM).